Association between mobility performance and severity of primary glaucoma - Rasidin, Abd Hadi Mohd (2022)
Glaucoma is the leading cause of irreversible blindness worldwide with primary open angle glaucoma (POAG) as the predominant subtype followed by primary angle closure glaucoma (PACG). Patients with advancing glaucoma suffer from increasing difficulty with daily living activities requiring peripheral vision which affects a broad array of activities that includes navigation and mobility at home. While there are effective medical interventions to minimize the progression of peripheral visual field loss in glaucoma, there is no cure the acquired field loss is irreversible. These limitations could be potentially be overcome by objective simulation of functional visual ability OBJECTIVE To compare mobility performance between patients with glaucoma and control and to associate with severity of glaucoma METHODOLOGY A cross sectional study was conducted involving patients with primary glaucoma and age-matched controls between June 2020 and June 2022 at Hospital Universiti Sains Malaysia (HUSM). Baseline visual assessment including visual acuity, contrast sensitivity, colour vision and Esterman binocular visual field were conducted. Patients with primary glaucoma were divided into severity of glaucoma based on the modified Hodapp-Anderson-Parish criteria on the visual field of their better eye. A mobility course arranged in a maze of 12-meters long and seeded with obstacles that represent furniture at home was created. The course was divided into four zones with fixed illumination and surveillance camera to observe the activities. Mobility performance was assessed by the time required to complete the course (in seconds) and number of mobility incidents which include bumps, stumbles, and orientation problem. RESULTS A total of 318 subjects (159 primary glaucoma and 159 controls) were recruited in this study. The mean time required by patients with primary glaucoma (53 mild, 54 moderate, and 52 severe) to complete the mobility course was 31.5 + 13.5 sec compared to 17.0 + 2.2 sec by the age-matched control (p<0.001). Those with severe glaucoma took longer time (46.8 + 15.2 sec) compared to mild (25.1 + 1.3 sec) and moderate (23.0 + 2.2 sec) (p<0.001). Patients with glaucoma have significant more mobility incidences (p<0.001). Mean mobility incidents were 4.9±3.2 and all were documented in patients with severe visual field of the better eye. Esterman visual field test showed strong negative correlation with mobility performance (r=-0.932) and contrast sensitivity showed moderate correlation (r=-0.520). The best distance between the furniture is 1.5 meter, while the distance of 0.5 meter reported 48 + 30.2 mobility incidence among patients with glaucoma. CONCLUSION Patients with glaucoma walk slower than the age-matched controls of which those with severe glaucoma walk the slowest. Mobility incidents were reported among those with severe glaucoma. Proper arrangement of furniture, good illumination and contrast sensitivity in their home environment may improve their navigation especially among those with severe disease